Concurrent fatigue and potentiation in endurance athletes - Boullosa, D. A.; Tuimil, J. L.; Alegre, L. M.; Iglesias, E.; Lusquinos, F. (International Journal of Sports Physiology and Performance, 2011)
Purpose: Countermovement jump (CMJ) and maximum running speed over a distance of 20 m were evaluated for examination of the concurrent fatigue and postactivation potentiation (PAP) in endurance athletes after an incremental field running test. Methods: Twenty-two endurance athletes performed two attempts of CMJ on a force plate and maximum running speed test before and following the Université de Montréal Track Test (UMTT). Results: The results showed an improvement in CMJ height (3.6%) after UMTT that correlated with the increment in peak power (3.4%), with a concurrent peak force loss (-10.8%) that correlated with peak power enhancement. The athletes maintained their 20 m sprint performance after exhaustion. Cluster analysis reinforced the association between CMJ and peak power increments in responders with a reported correlation between peak power and sprint performance increments (r = .623; P = .041); nonresponders showed an impairment of peak force, vertical stiffness, and a higher vertical displacement of the center of mass during the countermovement that correlated with lactate concentration (r = -0.717; P = .02). Conclusions: It can be suggested that PAP could counteract the peak force loss after exhaustion, allowing the enhancement of CMJ performance and the maintenance of sprint ability in endurance athletes after the UMTT. From these results, the evaluation of CMJ after incremental running tests for the assessment of muscular adaptations in endurance athletes can be recommended.